Target specificities of Drosophila Enhancer of split basic helix-loop-helix proteins. - Jennings, B.H.; Tyler, D.M.; Bray, S.J. (Molecular and Cellular Biology, 1999)
Seven Enhancer of split genes in Drosophila melanogaster encode basic-helix-loop-helix transcription factors which are components of the Notch signalling pathway. They are expressed in response to Notch activation and mediate some effects of the pathway by regulating the expression of target genes. Here we have determined that the optimal DNA binding site for the Enhancer of split proteins is a palindromic 12-bp sequence, 5'-TGGCACGTG(C/T)(C/T)A-3', which contains an E-box core (CACGTG). This site is recognized by all of the individual Enhancer of split basic helix-loop-helix proteins, consistent with their ability to regulate similar target genes in vivo. We demonstrate that the 3 bp flanking the E-box core are intrinsic to DNA recognition by these proteins and that the Enhancer of split and proneural proteins can compete for binding on specific DNA sequences. Furthermore, the regulation conferred on a reporter gene in Drosophila by three closely related sequences demonstrates that even subtle sequence changes within an E box or flanking bases have dramatic consequences on the overall repertoire of proteins that can bind in vivo.